Effect of Synbiotic Supplementation on Fatigue and Sleep Quality in End-stage Renal Disease Patients: A Randomized Clinical Trial - Mina Jangpour; Ali Asghar Jesmi; Akram Kooshki; Neda Mahdavifar; Ali Taj (Journal of Holistic Nursing and Midwifery)
Introduction: Chronic kidney disease is one of the public health issues in the world. Imbalances in the gut microbiome contribute to the progression of multiple diseases, including chronic kidney disease. The consumption of probiotics and synbiotics in treating various diseases has progressed significantly. Objective: The present study investigates the effects of synbiotic supplements on the intestinal microbiome, resulting in improving fatigue and sleep quality of end-stage renal disease patients undergoing hemodialysis. Materials and Methods: The study was a double-blind, randomized, placebo-controlled clinical trial. A total of 52 patients with end-stage renal disease undergoing hemodialysis were included in the research and, through permuted block randomization, assigned to the synbiotic group (28 patients) and the placebo group (24 patients). The intervention group received 500 mg of synbiotic (Lactocore) twice a day for eight weeks, and the control group received a placebo for the same period. The patients were evaluated with the Chalder fatigue and Pittsburgh sleep quality questionnaires at the beginning, the fourth week of the study, and at the end of the study. Demographic variables were analyzed using the chi-square test, Fisher exact test, or independent sample t-test, as appropriate. The repeated measures test was used because the outcome variable has been measured three times in each group. Results: The samples, consisting of 26 males (50%) and 26 females (50%), were randomly allocated to the placebo (n=24, 46.16%), 12 males and 12 females, and the synbiotic supplement (n=28, 53.84%), 14 males and 14 females, groups. The result showed regular use of a synbiotic supplement for 8 weeks did not show a change in the amount of fatigue and sleep quality reported in patients receiving the synbiotic supplement considering the effect of time and group compared to the placebo group. Conclusion: In general, the 8-week consumption of synbiotic supplements in the intervention group compared to the control group did not significantly affect the fatigue and sleep quality of patients undergoing hemodialysis treatment. However, further studies with larger sample sizes and longer duration are suggested.